Filariasis of Stensen’s Duct: An Index Case - Eishaan K. Bhargava; Nikhil Arora; Varun Rai; Ravi Meher; Prerna Arora; Ruchika Juneja (Case Reports in Otolaryngology)
Filariasis, a neglected tropical disease, is a global health problem and is endemic to 73 countries including India. It is caused by nematodes of Filariodidea family, namely, W. bancrofti and B. malayi in India, which have a predilection for the lower limbs and testis. We report a never before reported case of filariasis of the main parotid duct in a 25-year-old male that resolved on medical management, exemplifying the importance of maintaining a high index of suspicion and careful examination of cytological smears in endemic countries, allowing for an early diagnosis and treatment, decreasing the morbidity of this debilitating disease.